Silage production technology. - Philippine Council for Agriculture, Forestry and Natural Resources Research and Development (Los Banos, Laguna Philippine Council for Agriculture, Forestry and Natural Resources Research and Development, 2001)
This book gives information on ensiling and how it is practiced in farming. It gives an overview of what ensiling is how important it is and how it is done. It heightens the awareness of animal raisers in venturing into producing silage.
Keywords: Silage -- Philippines -- Handbooks, manuals, etc